Peningkatan Pemahaman Tokoh Proklamasi pada Mata Pelajaran IPAS Kelas VI melalui Media Pop-Up Book dan Permainan Interaktif Berbasis Website - Dinda Shalsa Agistie; Sartika; Salsa; Rijkha Silpiya Nur; Dita Salsabilla; Rana Gustian Nugraha (Jurnal keilmuan dan Kependidikan dasar, 2025)
History learning in elementary school often faces obstacles because history material tends to be abstract, making it difficult for students to understand key figures and important events. This condition was evident among sixth-grade students who showed low comprehension due to learning activities that were still dominated by lectures and simple media. This study aims to improve students’ understanding and engagement in the topic of Proclamation Figures through the use of Pop-Up Books and web-based interactive games. The method employed was Classroom Action Research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection. Data were collected through learning outcome tests, observations of student activity, and documentation. The results showed a significant improvement from Cycle I to Cycle II, where learning mastery increased from 62.5% to 93.75%, and the class average score rose from the “fair” to “excellent” category. In addition, students' engagement and motivation also improved through visual, kinesthetic, and interactive learning activities. Thus, the use of Pop-Up Books and interactive games is proven to be effective in creating more engaging and meaningful Social Studies learning and can serve as an alternative instructional media to enhance the quality of learning in elementary schools.